Thermal analysis of dual piezoelectric fans for cooling multi-LED packages - Shaker, Sufian Farid; Fairuz, Z. M.; Zubair, Mohammed; Abdullah, Mohd. Zulkifly; Mohamed, Julie Juliewatty (Pergamon Press, 2014)
This paper reports on the dissipation of heat generated by a high power LED array using piezoelectric fans. Both numerical and experimental studies were carried out to evaluate the heat dissipation efficiency of high power LED package operating under multiple vibrating fans. Two vibrating fans were vertically oriented to the LED package and arranged according to configuration A (for edge to edge arrangement), and configuration B (for face to face arrangement). The junction temperature (Tj), thermal resistance (R ) and average heat transfer coefficient View the MathML sourceh¯ were estimated. The results show that the single fan enhanced heat transfer performance approximately 1.8 times for the LED package. On the contrary, the dual fans enhanced heat transfer performance approximately by 2.3 times for configuration A and 2.4 for configuration B. A significant decrease in the thermal resistance was observed for all the configurations when fan separation distance δ was reduced. The best performance relative to natural convection was found to be at (δ = 0.1) which decreased the thermal resistance using single fan by about 38%, whereas the dual fan accounted for 49.5% in case of configuration A, and 50.6% for configuration B.